Protective Effects of Captopril and Spironolactone against Hyperglycemia-Induced Oxidative Stress in KGN Cells: Evidence from Viability and Mitochondrial Assays - Chandana; Ali, Mohammad; Bharathi, D.R (International Journal of Pharmaceutical Investigation, 2026)
Background Diabetes-induced oxidative stress adversely impacts ovarian granulosa cells, affecting fertility in women. This study explores the protective effects of captopril and spironolactone, two RAAS inhibitors, against STZ-induced damage in KGN cells. Materials and Methods KGN cells were exposed to STZ (5 mM) to induce oxidative stress, followed by treatment with captopril (10-50 µM), spironolactone (5-25 µM), or their combination. MTT, DCFDA, and JC-1 assays were conducted to assess cell viability, ROS generation, and mitochondrial membrane potential. Results STZ significantly increased ROS levels, reduced mitochondrial membrane potential (ΔΨm), and decreased cell viability. Both captopril and spironolactone improved these outcomes in a dose-dependent manner, with combination treatment showing the greatest protective effect. Conclusion Captopril and spironolactone confer cytoprotection to granulosa cells under hyperglycemic stress by reducing oxidative damage and preserving mitochondrial function. These findings support their potential repurposing in diabetic reproductive dysfunction therapy.
Keywords: Captopril; Spironolactone; Hyperglycemia; Granulosa Cells; Oxidative Stress; Mitochondrial Dysfunction; Reproductive Health.